Impact of the spatial structure of alkyl chains on properties of thiophene-substituted diketopyrrolopyrroles: Part I – Langmuir layer study - Stachowiak, Alicja; Kędzierski, Kamil; Rytel, Karol; Dudkowiak, Alina (Journal of molecular liquids, 2023)
[Display omitted] •Despite similarities in the molecular structures of the investigated DPP dyes, they behave differently in thin films.•Langmuir layer molecule area is one-third  of DFT-optimized dye structure calculations.•The presence of dimeric and tetrameric forms of the dyes in thin layers are postulated.•Branching of alkyl side chain leads to lowering of Langmuir layer stability. Slight changes in the dye structures may cause significant differences in molecular organization and aggregation ability of the dyes that determine their properties and usefulness for particular applications. The objects of our study were the dyes from the oligothiophene-substituted diketopyrrolopyrrole (DPP) group with alkyl chains in the terminal and side positions. The subject of our interest was to check the effect of the spatial structure (straight or branched) of DPP’s side alkyl chains on the dyes’ behavior in two-dimensional systems, the process of creating Langmuir layers at the air-water interface and the properties of Langmuir-Schaefer layers on a solid substrate. The course of isotherms of the dyes recorded during the compression process of Langmuir layers showed notable differences, and for the dye with a branched side alkyl chain, an isotherm inflection below 10 mN/m was observed. The process of layer formation was also thoroughly investigated using a Brewster angle microscope and measurements of changes in surface potential. Analysis of isotherms supported by density functional theory calculations suggests that the layers formed at the air-water interface are not monomolecular, consisting of monomers, but are built of aggregated (dimeric or tetrameric) dye forms. More stable layers were formed for the straight than branched alkyl side chains attached to the dyes. Morphologies of Langmuir-Schaefer layers transferred onto quartz were studied using confocal microscopy. The results confirmed that even a slight change in the spatial structure of the side alkyl chains of the investigated dyes determines their thermodynamic properties and organization of the thin film. Finally, a model of the arrangement of DPP dye molecules in thin layers was proposed.